Pengaruh Media Pembelajaran Multiply Cards terhadap Hasil Belajar Matematika Siswa Kelas IV SD Negeri Beroanging - Despryanto Despryanto; Sukmawati Sukmawati; Ernawati Ernawati (Lembag, 2025)
The study focuses on the influence of the Multiply Cards learning media on the mathematics learning outcomes of fourth-grade students at SD Negeri Beroanging. The main issue in this research is whether the Multiply Cards learning media affects the mathematics learning outcomes of fourth-grade students at SD Negeri Beroanging. This research is a quantitative study using an experimental method with a